한강원수로부터 분리된 수중휴믹물질의 계절적 분포와 분광학적 특성분석 - 김현철(Hyun Chul Kim); 이석헌(Seock Heon Lee); 김경주(Kyung Ju Kim); 유명진(Myong Jin Yu) (Daehan hwan'gyeong gonghag hoeji, 2007)
Humic substances(HS) from Han River water was physic-chemically isolated by fractionational methods to investigate the seasonal distribution and to characterize the properties compared with intrinsic humic materials. Various HS samples were analyzed by element, Fourier transform infrared(FT-IR), proton nuclear magnetic resonance$(^1H-NMR)$ and fluorescence analyzers. The portion of HS from Han River water(HRHS) was 47.0% on the average, however it appeared that rainfall event brought about higher fraction of HS in Han River water by the periodic investigation. Aromaticity and humification degree of the HRHS were relatively lower than those of intrinsic humic materials originated from decomposing vegetation. FT-IR, $^1H-NMR$ and fluorescence spectroscopy showed the distinct differences between HRHS and intrinsic humic materials. Commercial humic materials could not represent structural and functional characteristics of local HS. The fluorescence spectroscopy, a relatively simple measurement, was found most useful tool to estimate humification degree for humic materials from particular sources. 본 연구에서는 한강원수로부터 물리화학적인 분리방법으로 휴믹물질(HS; humic substances)을 분리하여 HS의 계절별 분포특성을 조사하고, 식물분해산물에 의한 유기물 구성이 지배적인 자연형 하천수로부터 추출된 HS와 함께 다양한 분광학적 특성분석을 통하여 구조화학적 특성을 비교하고 그 기원특성을 평가하였다. 한강원수로부터 분리된 HS(HRHS)의 구성분율은 연평균 47.0%로, 건기에 비해서 우기에 상대적으로 높은 것으로 나타났다. HRHS는 다른 지역의 수계에서 추출된 HS보다 방향성(aromaticity)과 부식화도 (humification degree)가 상대적으로 낮은 것으로 조사되었으며, 이는 수환경계에서 부식화가 진행되는 유기물질의 기원특성과 이들 물질이 축합반응(polymerization)에 기여하는 정도에 따라서 그 구조화학적 성질이 차이를 나타내기 때문으로 보인다. 적외선분광(FT-IR)과 양성자핵자기공명$(^1H-NMR)$ 그리고 형광(fluorescence)분석은 HRHS와 상용화된 HS 간의 구조화학적 차이를 명확히 나타내었으며, FT-IR 및 $^1H-NMR$과 같은 전통적인 분광분석법에 비해서 상대적으로 단순화된 전처리과정과 짧은 응답시간을 요하는 형광분석법이 분석절차상 HS의 방향성 및 부식화도를 평가하기 위한 가장 효율적인 분석수단으로 평가되었다.